Exhausted CD8+T Cells in the Tumor Immune Microenvironment: New Pathways to Therapy - Jiang, Weiqin; He, Yinjun; He, Wenguang; Wu, Guosheng; Zhou, Xile; Sheng, Qinsong; Zhong, Weixiang; Lu, Yimin; Ding, Yongfeng; Lu, Qi; Ye, Feng; Hua, Hanju (Frontiers in Immunology, 2021)
Tumor-specific CD8+T cells are exposed to persistent antigenic stimulation which induces a dysfunctional state called “exhaustion”. Though balancing limits activation-induced immunopathology, T cell exhaustion leads to attenuated effector function whereby cytotoxic CD8+T cells fail to control tumor progression in the late stage. This pathway is a dynamic process from activation to “progenitor exhaustion” through to “terminally exhaustion”. With the rapid development of immunotherapy via enhancing T cell function, new studies are dissecting the mechanisms and identifying specific biomarkers of dynamic differentiation during the process of exhaustion. Further, will administration of immune checkpoint inhibitors (ICIs) have achieved great success in clinical practice, most patients still show limited efficacy to ICIs. Thus, exploring tumor specific properties in the dynamic exhaustion phase may help identify rational and more effective ICI combination strategies. In this review, we aim to introduce the concept of homeostasis of the activated and exhausted status of CD8+T cells in the tumor immune microenvironment, and present recent findings on dynamic differentiation process during T cell exhaustion and the implications for combination strategies in immune therapy.